PEGAWAI HEBAT LAHIR DARI LINGKUNGAN KERJA YANG MENDORONG DAN DISIPLIN YANG KUAT - Aryanto, Tossy; HARTARINI, YOVITA MUMPUNI; Khayatun, Siti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
This study aims to determine (1) the effect of work motivation on employee performance, (2) the effect of work environment on employee performance, (3) the effect of work discipline on employee performance, and (4) the simultaneous effect of work motivation, work environment, and work discipline on employee performance. This research is classified as causal-associative research using a saturated sampling (census) technique. The subjects of this study were 31 employees of the National Unity and Political Agency (Badan Kesatuan Bangsa dan Politik) of Kendal Regency. Data were collected through questionnaires, and the research instruments were tested using validity and reliability tests. The classical assumption tests included normality, multicollinearity, and heteroscedasticity tests. Data analysis was carried out using multiple linear regression, the coefficient of determination (R²), and t-test and F-test. The results showed that: (1) Work motivation has a positive and significant effect on employee performance, with a t-value of 4.016 greater than the t-table value of 1.70 and a significance value of 0.000 < 0.05. This means that higher work motivation leads to higher employee performance, thus H1 is accepted. (2) The work environment has a positive and significant effect on employee performance, with a t-value of 4.428 greater than the t-table value of 1.70 and a significance value of 0.002 < 0.05. Therefore, H2 is accepted, indicating that a better work environment improves employee performance. (3) Work discipline has a positive and significant effect on employee performance, with a t-value of 2.625 greater than the t-table value of 1.70 and a significance value of 0.017 < 0.05. Thus, H3 is accepted, meaning that better work discipline increases employee performance. (4) The simultaneous test shows a significance value of 0.000 < 0.05, indicating that work motivation, work environment, and work discipline jointly have a significant effect on employee performance at the National Unity and Political Agency of Kendal Regency, and therefore H4 is accepted. Based on the research findings, management needs to pay greater attention to motivation, work environment, and work discipline to enhance employee performance, particularly in the aspect of work discipline, which showed the lowest beta value compared to motivation and work environment.